1998
DOI: 10.1074/jbc.273.29.18325
|View full text |Cite
|
Sign up to set email alerts
|

Cain, A Novel Physiologic Protein Inhibitor of Calcineurin

Abstract: Calcineurin is a widely distributed protein phosphatase regulated by calcium and calmodulin. It mediates the immunosuppressive actions of drugs such as cyclosporin and FK506, and has been implicated in a number of calcium-sensitive pathways in the nervous system, including regulation of neurotransmitter release and modulation of long-term changes in synaptic plasticity. Calcineurin associates physiologically with other proteins, including calmodulin, FKBP12 (FK506-binding protein), the ryanodine receptor, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(173 citation statements)
references
References 52 publications
2
170
0
1
Order By: Relevance
“…CAIN (also known as Cabdin) acts as a physiological non-competitive inhibitor of calcineurin and both proteins are components of the endocytotic machinery [50]. Overexpression of CAIN in HEK293 cells blocked endocytosis [51]. Thus decreased levels of CAIN could also favour endocytosis in insulin-producing cells.…”
Section: Discussionmentioning
confidence: 99%
“…CAIN (also known as Cabdin) acts as a physiological non-competitive inhibitor of calcineurin and both proteins are components of the endocytotic machinery [50]. Overexpression of CAIN in HEK293 cells blocked endocytosis [51]. Thus decreased levels of CAIN could also favour endocytosis in insulin-producing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that CnABP is a substrate for calcineurin with its own NFAT-independent cellular activity, as is the case for the K + channel TRESK (54). In this respect, it is remarkable that the best-conserved domain of CnABP contains a perfect PxIxIT consensus sequence (where x represents any amino acid), which is a calcineurin docking site found in NFATs and other calcineurin substrates (54,55), as well as in calcineurin inhibitor proteins such as Cain/Cabin1 and A238L (56)(57)(58). This sequence was shown to be sufficient for binding to calcineurin (59).…”
Section: Regulation Of Calcineurin Signaling By Cnabpmentioning
confidence: 99%
“…It has been reported that in response to PKC activation Cabin 1 becomes hyperphosphorylated exhibiting a higher affinity for calcineurin, and the binding of Cabin 1 to the enzyme inhibits its activity (7,9). To investigate the possible role of Cabin 1 in this signalling pathway, Cabin 1 was immunoprecipitated with a polyclonal antibody.…”
Section: Cabin 1 As a Signal Transducer Between Pkc And Calcineurinmentioning
confidence: 99%
“…Cabin 1 is hypophosphorylated in non-activated T cells, and in response to protein kinase C (PKC) activation, it becomes hyperphosphorylated exhibiting a higher affinity for calcineurin. It has been reported that the interaction between Cabin 1 and calcineurin requires both calcium signalling and activation of PKC (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%